Peran Guru Pendidikan Agama Kristen dalam Membentuk Karakter Kristiani Siswa di SMK Negeri 1 Beringin - Metra Kartini Simanungkalit (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the role of Christian Religious Education (PAK) teachers in shaping the Christian character of students at SMK Negeri 1 Beringin. This study uses a qualitative approach with a literature study method and secondary data analysis. The results of the study indicate that PAK teachers have a strategic role as educators, mentors, facilitators, and advisors in instilling Christian values ​​such as love, honesty, responsibility, forgiveness, and concern for others. Character formation is carried out through the teacher's exemplary life, integration of Biblical values ​​in the learning process, application of real faith practices in everyday life, and a learning approach that prioritizes love and understanding of students' needs. In addition, PAK teachers are expected to continue to develop themselves spiritually and professionally to increase equal effectiveness. Suggestions from this study include the importance of improving the quality and competence of teachers, providing supporting facilities and infrastructure by schools, and developing contextual, interactive, and relevant learning methods to students' lives so that Christian character formation can take place optimally.